2020
DOI: 10.1182/blood-2020-134538
|View full text |Cite
|
Sign up to set email alerts
|

Early Versus Late Autologous Stem Cell Transplant in Newly Diagnosed Multiple Myeloma: Long-Term Follow-up Analysis of the IFM 2009 Trial

Abstract: Introduction The IFM 2009 study prospectively evaluated the combination of 8 cycles of lenalidomide, bortezomib and dexamethasone (RVd) versus (vs) 3 cycles of RVd plus high dose (HD) melphalan with autologous stem cell transplantation (ASCT) plus 2 consolidation RVd cycles, followed by lenalidomide maintenance for 12 months (mo) in newly diagnosed multiple myeloma (NDMM) patients (Attal M et al, NEJM 2017). RVd with transplant was associated with significantly longer progression-free survival (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 0 publications
1
68
0
7
Order By: Relevance
“…The investigators found 30% and 20% MRD negativity rates in the two study arms, respectively; this translated into 14 months longer median progression‐free survival in the treatment arm including upfront HDM‐ASCT; however, there was no difference in overall survival 17 . At the American Society of Hematology (ASH) 2020 meeting, updated results from the same study with a median follow‐up of 8 years continued to show no overall survival difference between the two treatment arms 4 . In 2021, the utility of upfront vs delayed HDM‐ASCT remains an area of controversy in the myeloma field 18‐21 .…”
Section: Introductionmentioning
confidence: 99%
“…The investigators found 30% and 20% MRD negativity rates in the two study arms, respectively; this translated into 14 months longer median progression‐free survival in the treatment arm including upfront HDM‐ASCT; however, there was no difference in overall survival 17 . At the American Society of Hematology (ASH) 2020 meeting, updated results from the same study with a median follow‐up of 8 years continued to show no overall survival difference between the two treatment arms 4 . In 2021, the utility of upfront vs delayed HDM‐ASCT remains an area of controversy in the myeloma field 18‐21 .…”
Section: Introductionmentioning
confidence: 99%
“…While the DFCI study is still awaiting final outcomes, the IFM study showed that upfront ASCT in patients with NDMM resulted in significantly longer PFS compared to those without. The benefit was seen across all stages and cytogenetic risk groups [ 55 ]. However, there was minimal overall survival benefit seen in the transplant group.…”
Section: Conditioning Chemotherapymentioning
confidence: 99%
“…Lenalidomide maintenance was given in both arms for 13 cycles. PFS was increased in the transplant-arm (47.3 m vs. 35.0 m; p = 0.0001), but even after extended follow-up [ 38 ], no differences in PFS2 or OS have been observed. However, 201 patients in the non-transplant arm received transplant at relapse.…”
Section: Current Use Of “Old” Alkylating Agentsmentioning
confidence: 99%